(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The paper aims at giving a contribution for the elaboration of a common lexicon in the field of end of life issues. In particular, the beginning of a new phase for the political debate in Italy (with the introduction of some new legislative proposals on informed consent, end of life issues and living wills) requires a reflection upon some concepts of central importance for the debate. Among them, the meaning of artificial nutrition – as distinct from feeding – and its qualification as a medical treatment is essential for the construction of a conscious political discussion, in which the legal as well the medico-scientific dimension could obtain due consideration.